Materials and Osseointegration Processes in Dental Implants: A Systematic Review - Susanna Halim; Niki Yuchinda; Jessica Angelie; Annisa Rizkia Ginting; Vonny Maria (Journal of Science and Science Education, 2026)
Tooth loss is a common oral health problem that affects chewing ability, appearance, and quality of life. Dental implants have become the most effective solution to restore both function and aesthetics. The success of dental implants depends on biomaterial composition and the osseointegration process between the implant and the alveolar bone. This study analyzed recent advancements in implant materials, surface modifications, and biological factors influencing osseointegration and long-term stability. A randomized clinical trial compared zirconia and titanium implants, evaluating various surface treatments and the use of nano-hydroxyapatite as a bioactive material to enhance osseointegration. Results showed that titanium and zirconia remain dominant implant materials, with clinical success rates above 90%. Surface treatments such as sandblasting, anodization, and nano-hydroxyapatite coating significantly improved osseointegration. Moreover, the application of Platelet-Rich Plasma (PRP) and Platelet-Rich Fibrin (PRF) accelerated tissue healing. Systemic conditions like diabetes, bone quality, and surgical techniques also affected outcomes. Overall, innovations in biomaterials and surface engineering have enhanced implant stability, aesthetics, and durability, showing great promise in improving clinical success and patients’ quality of life